Improving the Resilience of Freight Forwarding Companies using Supply Chain Finance - Wisudanto, Wisudanto; Thalib , Prawitra; Panjaitan, Selvy; Nuryadi, Fredy (Sebatik, 2024)
The industrial revolution 4.0 has expanded business and economic transactions beyond the domestic sphere, fostering interactions between countries. This shift necessitates business entities that can facilitate seamless international transactions. Freight forwarding, as a key player in the logistics sector, plays a crucial role in enabling the movement of goods and services across international borders. However, freight forwarding companies face challenges from fluctuations in foreign exchange rates due to transactions involving suppliers and consumers from various countries, making them vulnerable to currency exchange rate volatility. This paper aims to understand the financial business processes of freight forwarding companies, particularly in managing financial risks and addressing currency exchange rate fluctuations. Additionally, it seeks to explore strategies to minimize the negative impact of exchange rate fluctuations on the financial stability of these companies. The research methodology is descriptive, employing surveys and interviews with freight forwarding companies and stakeholders in the logistics industry. Data triangulation with relevant agencies ensures more valid and comprehensive insights into how the industry addresses currency exchange rate challenges. The findings suggest that freight forwarding companies can mitigate losses from exchange rate fluctuations by implementing hedging strategies and adopting supply chain finance practices on an ongoing basis.